Collaborative Governance Dalam Pencegahan dan Penanggulangan Humas Immunodeficiency Virus (HIV) dan Acquired Immunodeficiency Syndrom (AIDS) di Kota Palu - sumaso, Muriani Lan; Halim, Rahmawati; Firmansyah , Andi Maman (JPS: Journal of Publicness Studies, 2025)
Collaborative Governance between the Palu City Health Office, AIDS Commission, and Indonesian Women's Association Legal Association for Justice (LBH Apik), in the prevention and prevention of HIV/AIDS in Palu City, still faces challenges such as formal documents that are still limited, coordinations that have not yet reached across actors, as well as limited resources owned by the IADS Commission (KPA) of Palu City. This study aims to determine collaborative governance in the prevention and prevention of HIV/AIDS in Palu City. This study uses the theory of collaborative governance by Emerson, Nabatchi & Blogh (2012) covering three aspects, namely: Principled Edugament/Involvement of Principles, Shared Motivatiaon/Motivation together, and Capaty for Join Action/Capacity to take action together. The basis of this research is qualitative, with the type of research namely descriptive. The informant consists of the elements of the actor who collaborates, namely from the Palu City Health Office, KPAIDS, and LBH APK. Types of data in the form of primary and secondary data, with data collection techniques, namely interactive models by Miles, Huberman, and Saldana (2014) including data collection, data condensation, data presentation, and drawing conclusions. The results of this study show that collaborative governance in the prevention and prevention of HIV/AIDS in Palu City. less than optimal. Aspects of principled engagement/involvement indicate a collaboration between key actors in the prevention and prevention of HIV/AIDS in the City of Palu between the City Health Office, the City AIDS Management Commission, and LBH APIK Central Sulawesi. Shared Motivation aspects, namely the implementation of mutual trust, communication that is built, and sharing information. The capacity for join action aspects are the inactivation of the Working Group and Memoroundon of Understanding (MoU) that have not been implemented as a whole in the actors.